2023
DOI: 10.3390/genes14071445
|View full text |Cite
|
Sign up to set email alerts
|

D-Type Cyclins in Development and Disease

Mostafa Saleban,
Erica L. Harris,
James A. Poulter

Abstract: D-type cyclins encode G1/S cell cycle checkpoint proteins, which play a crucial role in defining cell cycle exit and progression. Precise control of cell cycle exit is vital during embryonic development, with defects in the pathways regulating intracellular D-type cyclins resulting in abnormal initiation of stem cell differentiation in a variety of different organ systems. Furthermore, stabilisation of D-type cyclins is observed in a wide range of disorders characterized by cellular over-proliferation, includi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 114 publications
0
5
0
Order By: Relevance
“…Considering that D-type cyclins do not possess any enzymatic function, nowadays one of the most promising strategies to tackle cyclin D-based disorders involves targeting the enzymatic activity of their partners (CDK4 and CDK6), even though this approach may lead to toxic side effects due to lack of selectivity of the currently available inhibitors. 23 Of note, in the literature it is also reported that EGFR activation promotes NSCLC cell migration through the secretion of cathepsin B by NEDD4 E3 ubiquitin ligase. Upon binding of its specific ligands, activated EGFR also stimulates the release of calcium from the ER pool to the cytoplasm, and as a result, the NEDD4 protein is activated and recruited to the EGFR-loaded endosomes.…”
Section: Structure and Egfr Signaling Pathway In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that D-type cyclins do not possess any enzymatic function, nowadays one of the most promising strategies to tackle cyclin D-based disorders involves targeting the enzymatic activity of their partners (CDK4 and CDK6), even though this approach may lead to toxic side effects due to lack of selectivity of the currently available inhibitors. 23 Of note, in the literature it is also reported that EGFR activation promotes NSCLC cell migration through the secretion of cathepsin B by NEDD4 E3 ubiquitin ligase. Upon binding of its specific ligands, activated EGFR also stimulates the release of calcium from the ER pool to the cytoplasm, and as a result, the NEDD4 protein is activated and recruited to the EGFR-loaded endosomes.…”
Section: Structure and Egfr Signaling Pathway In Cancermentioning
confidence: 99%
“…The dysregulation of CCND1 irremediably compromises the S-phase checkpoint, inducing forced progression of the cell cycle, disrupting DNA replication, and therefore promoting DNA damage and genomic instability, resulting in oncogenesis. Considering that D-type cyclins do not possess any enzymatic function, nowadays one of the most promising strategies to tackle cyclin D-based disorders involves targeting the enzymatic activity of their partners (CDK4 and CDK6), even though this approach may lead to toxic side effects due to lack of selectivity of the currently available inhibitors …”
Section: Structure and Egfr Signaling Pathway In Cancermentioning
confidence: 99%
“…After 48 h treatment, IC50 for OLE was 350 μM. OLE induced cell cycle arrest and apoptosis through upregulation of CDK inhibitors p53, p21 WAF1/Cip1 , p15 INK4b , and p16 INK4a , together with downregulation of cyclins D1, D2, and D3, and CDK4 and CDK6 [ 92 , 115 , 218 , 219 ]. HT was also effective in the reduction in cell viability of SH-SY5Y cells after 72 h incubation, with mean EC50 ± S.D.…”
Section: Effects Of Ole and Ht On Solid Tumorsmentioning
confidence: 99%
“…The literature on cyclin D also reported its additional functions, such as the sequestration of two important CKIs p21 and p27 [33], phosphorylation of other transcription factors involved in the regulation of the cell cycle Smad3 and forkhead box M1 (FOXM1) [34], effects on mitochondrial metabolism [35], and the effects in the cellular response to genotoxicity [36]. The available evidence seems to suggest that transcription and activity of cyclin D are significantly reliant on the mitogenic signals from three key signaling pathways: the MAPK pathway (Ras/Raf/MEK-ERK for cyclin D synthesis), the PI3K/Akt pathway (for cyclin D stability), and the Wnt/ß-catenin pathway (ß-catenin/TCF-LEF) [37]. Moreover, the transcription of cyclin D can also be regulated by other signals, such as the Notch pathway, extracellular matrix, cytokines (through STAT3), and immune signals (through nuclear factor kappa B, NF-κB) [27].…”
Section: Ellagic Acid and Sustaining Proliferative Signalingmentioning
confidence: 99%
“…However, their levels may differ depending on the particular tissue and type of cancer. Next, it has been reported that their oncogenic potential is typically linked to genetic deregulation, often stemming from gene amplification, mutations, or other genetic alterations [37]. Interestingly, the amplification of CCND1 was found to be the most frequently observed genetic event in cancer [39].…”
Section: Ellagic Acid and Sustaining Proliferative Signalingmentioning
confidence: 99%